Les différents traités environnementaux sont-ils appropriés pour les populations des pays en développement (Afrique) ? - D.E Musibono; F. Kabangu; A. Munzundu; M. Kisangala; I. Nsimanda; M. Sinikuna; A. Kileba (VertigO)
This paper reports on the level of the implementation for various environmental conventions ratified by the DR Congo, especially that on Biodiversity and CITES. This study was carried out at Kinshasa, the capital city of the Democratic Republic of Congo. We focused on bush meat markets. Results revealed that traders ignore these conventions and have never heard about them. This seems particularly due to poor environmental communication. Another reason is the lack of secured alternative source incomes for family livelihood. This paper also revealed the application weaknesses of treaties, conventions and protocols without community participation. Things are generated and imposed from the top, and of course they seem very strange to the community at grass root level. It is why we recommend the strengthening of the environmental communication service to better inform the population about the environmental policy and conventions ratified.